2010
DOI: 10.1007/s00592-010-0184-6
|View full text |Cite
|
Sign up to set email alerts
|

White rice vinegar improves pancreatic beta-cell function and fatty liver in streptozotocin-induced diabetic rats

Abstract: Vinegar is a traditional remedy for ailments including diabetes. This study was conducted to investigate the beneficial effects of vinegar in streptozotocin (STZ)-induced diabetic rats. STZ-induced diabetic rats were orally administered with white rice vinegar (WRV, 2 ml/kg body weight per day, n = 6) or with an equal volume of drinking water (n = 6) for 1 month. Fasting and random blood glucose was measured from tail vein samples. Body weight, 24-h food and water intake were monitored 1 week and 1 month after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 23 publications
2
24
0
3
Order By: Relevance
“…Gu et al (2012) found that the consumption of Chinese white rice vinegar helped in controlling blood glucose; Fan et al (2011) obtained similar results, verifying inhibitory activity of α-glucosidase, which can be useful for diabetics. Other studies have demonstrated benefits across the immune system (Hashimoto et al, 2013) and anti-hypertensive effect (Kondo et al, 2001).…”
Section: Functional Properties Of Vinegarmentioning
confidence: 79%
See 2 more Smart Citations
“…Gu et al (2012) found that the consumption of Chinese white rice vinegar helped in controlling blood glucose; Fan et al (2011) obtained similar results, verifying inhibitory activity of α-glucosidase, which can be useful for diabetics. Other studies have demonstrated benefits across the immune system (Hashimoto et al, 2013) and anti-hypertensive effect (Kondo et al, 2001).…”
Section: Functional Properties Of Vinegarmentioning
confidence: 79%
“…White rice vinegar may have antiglycemic function (Salbe et al, 2009;Gu et al, 2012), brown rice vinegar (kurosu) has benefits across the immune system (Hashimoto et al, 2013) and antitumor effect, for example (Fukuyama et al, 2007). Gu et al (2012) found that the consumption of Chinese white rice vinegar helped in controlling blood glucose; Fan et al (2011) obtained similar results, verifying inhibitory activity of α-glucosidase, which can be useful for diabetics.…”
Section: Functional Properties Of Vinegarmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other products, rice vinegar given to diabetic rats has improved insulin secretion by the pancreas and postprandial hyperglycemia (Gu, Zhao et al 2012). Positive effects of fiber have emerged in a study on Goami-3 rice, a variety with high levels of amylose and fiber.…”
Section: Diabetes and Metabolic Syndromementioning
confidence: 99%
“…Some kinds of vinegars are also used to treat diseases in traditional Chinese medicine. Many studies have also indicated that vinegar has a wide spectrum of physiological effects, such as alleviating exhaustion, preventing obesity, and regulating blood pressure and blood glucose (Fan et al 2009;Gu et al 2012;Kahramani et al 2011;Kondo et al 2001;Sugiyama et al 2003). In addition, it can be used as a natural insecticide, antigermination agent, and termiticide.…”
Section: Introductionmentioning
confidence: 99%